Understanding intercultural communication : negotiating a grammar of culture - Holliday, Adrian (Routledge, 2013)
"In this book, Adrian Holliday provides a practical framework to help students analyse intercultural communication. Underpinned by a new grammar of culture developed by Holliday, this book will incorporate examples and activities to enable students and professionals to investigate culture on very new, entirely non-essentialist lines. This book will address key issues in intercultural communication including: the positive contribution of people from diverse cultural backgrounds, the politics of Self and Other which promote negative stereotyping, the basis for a bottom-up approach to globalization in which Periphery cultural realities can gain voice and ownership. Written by a key researcher in the field, this book presents cutting edge research and a framework for analysis which will make it essential reading for upper undergraduate and postgraduate students studying intercultural communication and professionals in the field"--EBL